PEMBUATAN WEBSITE SEBAGAI SARANA UNTUK MEMPROMOSIKAN ORGANISASI PROFESI - Jeanny Pragantha; Endah Setyaningsih; Sacchio Orlando; Harley Leo Liman (PROSIDING SERINA, 2021)
HTII (Himpunan Teknik Iluminasi Indonesia or Indonesian Illuminating Engineering Society) is a professional organization whose members are people who meet qualifications in the field of illumination based on education, experience, and expertise in the lighting field and who have great interest in this field. This organization was founded on May 7, 1991 in Jakarta by Ir. T W Simbolon, MSc and Ir. Ketut Kontra, MSc. One of the visions and missions of HTII is the implementation of the construction and management of illumination facilities by Indonesian workers and cooperating with related institutions, associations/organizations, and industries, either directly or indirectly, either nationally or internationally. At the age of 30, not many people know about this organization. Social media Instagram is the only way to inform HTII's activities to public. With only 318 followers, it shows that this organization is less well known to the public. The HTII website was designed which aims to introduce and promote HTII activities to the general public. To create an HTII website, it is necessary to prepare hardware that can run the website to be created, namely Shared hosting that supports PHP and MySQL databases as well as software with minimum specifications, namely MySQL Database version 5.7; PHP version 7, the latest web browsers such as Google Chrome, Firefox, Safari, and the like. The HTII website can be accessed at: http/htii.or.id. With this website, it is hoped that HTII can be better known to the public through the information displayed and website users can relate to HTII.